Parametric sensitivity analysis of Aerodynamic stability for planar membrane structures. Issue 1 (July 2021) - Du, Lingling; Song, Weiju
Abstract: To explore the influence of design parameters on the aerodynamic stability of planar membrane structures, a mathematical model for calculating the critical wind speed of flat panel structures was established, and the closed expression of the critical wind speed was obtained through the criterion of instability. The influence of membrane size, membrane density, pretension and other parameters on the critical wind speed was studied by monofactor analysis. The results show that, with the help of the new concept of benefit loss coefficient, the sensitivity analysis of instability critical wind speed parameters can be easily carried out, and many qualitative and quantitative laws can be obtained.